Polimorfizmi gena MTHFR i njihove biohemijske asocijacije sa vitaminom D u serumu i IL-17 u ulceroznom kolitisu: MTHFR Variants and Biochemical Markers in Ulcerative Colitis - Chen, Guang; Yan, Meihong; Hu, Xiaoyang; Xu, Hanfei; Piao, Shengai (Journal of Medical Biochemistry, 2026)
Background: Disturbances in homocysteine metabolism and immune-inflammatory pathways may contribute to the pathogenesis of ulcerative colitis (UC). Methylenetetrahydrofolate reductase (MTHFR) plays a central biochemical role in homocysteine remethylation, and its genetic variants may influence downstream biomarkers such as vitamin D and interleukin-17 (IL-17). This study examined the associations of three MTHFR polymorphisms (rs110298, rs132981, rs167281) with UC susceptibility, disease characteristics, and related biochemical markers.Patients and methods: A total of 124 UC patients and 128 healthy controls were enrolled. Genotyping of MTHFR SNPs was performed by PCR amplification followed by ligase detection reaction. Serum 25-hydroxyvitamin D was measured using electrochemiluminescence immunoassay, and IL-17 levels were quantified by ELISA. Associations between MTHFR genotypes, UC onset, disease location, severity, and biochemical markers were statistically evaluated.Results: All polymorphisms conformed to Hardy–Weinberg equilibrium. The rs110298 GG genotype and rs132981 TT genotype were significantly more frequent in UC patients than controls (P < 0.05), whereas rs167281 showed no association with UC. Both rs110298 and rs132981 were linked to UC disease location and severity (P < 0.05). UC patients exhibited significantly reduced serum vitamin D and elevated IL-17 levels compared with controls (P < 0.05). Importantly, rs110298 (AG/GG) and rs132981 (TT) genotypes were associated with lower vitamin D and higher IL-17 concentrations in UC patients (P < 0.05), indicating a biochemical effect of MTHFR variants on inflammatory and immunomodulatory pathways.Conclusions: MTHFR polymorphisms rs110298 and rs132981 are significantly associated with UC susceptibility and clinical phenotype and exert measurable biochemical effects on serum vitamin D and IL-17 levels. These findings highlight the potential value of MTHFR-related pathways as biomarkers for disease characterization and as mechanistic contributors to UC-related immune dysregulation.